“Being Married Doesn’t Mean You Have to Reach the End of the World”: Safety Planning With Intimate Partner Violence Survivors and Service Providers in Three Urban Informal Settlements in Nairobi, Kenya - Wood, Shannon N. (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) harms women physically, sexually, and psychologically. Safety strategies, or harm reduction techniques implemented by women undergoing recurrent violence, may help mitigate the negative health, economic, and social consequences of IPV. This study aimed to understand recommended and utilized safety strategies among three urban informal settlements in Nairobi, Kenya. Semi-structured key informant discussions (KIDs; n = 18) with community-based service providers and focus group discussions (FGDs; n = 49) with IPV survivors were conducted. All interviews were audio-recorded, transcribed, and translated verbatim from Swahili to English. Inductive thematic analysis was used to structure codes. Convergence matrices were used to analyze emergent strategies by data source (service providers vs. IPV survivors). Women preferred safety strategies that they could implement unassisted as first line of harm reduction. Strategies included removing stressors, proactive communication, avoidance behaviors, sexual and reproductive health (SRH), economic, leaving partner for safety, child safety, and securing personal property. Strategies recommended by service providers and utilized by IPV survivors differed, with clear divergence indicated for leaving the abusive relationship, SRH, and personal property strategies. Innovative strategies emerged from IPV survivors for safeguarding property. Similar to upper-income and other low and middle-income contexts, women experiencing IPV in urban informal settlements of Nairobi actively engage in behaviors to maximize safety and reduce harm to themselves and their families. Integration of strategies known to be helpful to women in these communities into community-based prevention and response is strongly encouraged. Increased synergy between recommended and implemented safety strategies can enhance programming and response efforts.